Induction of Human Factor VIII Inhibitors in Rats by Immunization with Human Recombinant Factor VIII: a Small Animal Model for Humans with High Responder Inhibitor Phenotype - Jarvis, M A; Levin, L G; Harrison, J A; DePianto, D J; Suzuki, C M; Ziaja, C L; Brown, J E; Jolly, K W; Reisner, H M; Abidgaard, C F; Powell, J S (Thrombosis and Haemostasis, 1996)
Hemophilia A is a clotting disorder that is due to reduced or absent coagulation factor VIII (FVIII) activity. In approximately 25% of people with severe hemophilia A, standard treatment with intravenous plasma-derived or recombinant FVIII (rFVIII) induces anti-FVIII antibodies that inhibit FVIII activity (inhibitors). We describe the development of a rat model to study the formation of inhibitors. Immunization of rats with human rFVIII in adjuvant induced an anti-human rFVIII antibody response characteristic of an anti-FVIII inhibitor response in hemophilia A patients. The rats exhibited a rapid, polyclonal secondary antibody response to human rFVIII. These antibodies were reactive against epitopes located in the heavy and light chains. All the rFVIII-immunized rats developed antibodies against the FVIII C2 domain, a region of major reactivity in hemophilia A patients with inhibitors. Furthermore, competition ELISAs demonstrated that rat and human anti-FVIII antibodies recognized identical or overlapping epitopes of the FVIII molecule. The rat anti-FVIII antibodies also functioned as human FVIII inhibitors with titers ranging from 120 to 2048 Bethesda Units (B.U.). We propose that this rat model may be useful to investigate immune responses to FVIII and may lead to better therapies for FVIII inhibitors.